Netupitant, a Potent and Highly Selective NK1 Receptor Antagonist, Alleviates Acetic Acid-Induced Bladder Overactivity in Anesthetized Guinea-Pigs - Palea, Stefano; Guilloteau, Véronique; Rekik, Moéz; Lovati, Emanuela; Guerard, Marc; Guardia, Maria-Alba; Lluel, Philippe; Pietra, Claudio; Yoshiyama, Mitsuharu (Frontiers in Pharmacology, 2016)
Introduction. Tachykinins potently contract the isolated urinary bladder from a number of animal species and play an important role in the regulation of the micturition reflex. On the guinea-pig isolated urinary bladder we examined the effects of a new potent and selective NK1 receptor antagonist (netupitant) on the contractions induced by a selective NK1 receptor agonist, SP-methylester (SP-OMe). Moreover, the effects of netupitant and another selective NK1 antagonist (L-733,060) were studied in anesthetized guinea-pigs using two experimental models, the isovolumetric bladder contractions and a model of bladder overactivity induced by intravesical administration of acetic acid (AA). Methods and Results. Detrusor muscle strips were mounted in 5 mL organ baths and isometric contractions to cumulative concentrations of SP-OME were recorded before and after incubation with increasing concentrations of netupitant. In anesthetized female guinea-pigs, reflex bladder activity was examined under isovolumetric conditions with the bladder distended with saline or during cystometry using intravesical infusion of AA. After a 30 min stabilization period, netupitant (0.1–3 mg/kg, i.v.) or L-733,060 (3–10 mg/kg, i.v.) were administered. In the detrusor muscle, netupitant produced a concentration-dependent inhibition (mean pKB = 9.24) of the responses to SP-OMe. Under isovolumetric conditions, netupitant or L-733,060 reduced bladder contraction frequency in a dose-dependent manner, but neither drug changed bladder contraction amplitude. In the AA model, netupitant dose-dependently increased intercontraction interval (ICI) but had no effect on the amplitude of micturition (AM). L-733,060 dose-dependently increased ICI also but this effect was paralleled by a significant reduction of AM. Conclusion. Netupitant decreases the frequency of reflex bladder contractions without altering their amplitude, suggesting that this drug targets the afferent limb of the micturition reflex circuit and therefore may be useful clinically in treating bladder overactivity symptoms.